Echocardiographic Assessment of Left Ventricular Mass Regression and Functional Changes after Bariatric Surgery (Medical Forum Monthly, 2026)
Objective: To determine the echocardiographic outcomes of left ventricular mass and diastolic functions in obese patients undergoing bariatric surgery.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Al-Batool Hospital (Bariatric Surgery Clinic) between the period of 1st January 2025 and 31st July 2025.Methods: Enrolment of 51 adult participants was done at the age of 18-65 years. The mass of the left ventricles and the index of diastolic functions were determined preoperative and postoperative through conventional twodimensional transthoracic echocardiography.Results: Bariatric surgery showed a substantial decrease on mean left ventricular mass (139.274141.3 g) relative to preoperation levels (175.9648.4 g; p<0.05). It was revealed that postoperative assessment showed A-wave velocity and E / e + ratio declined significantly (p<0.05), whereas e 2 velocity and E / A ratio increased significantly after surgery (p<0.05). The velocity of the E-wave did not differ significantly between the pre and postoperative measurements (p > 0.05).Conclusion: Bariatric surgery enhances diastolic improvement and regression of left ventricular mass in obese patients, indicating substantial cardiac remodelling.